Analisis dan Desain Sistem Informasi Pemesanan Menu Makanan Berbasis Web Menggunakan Model Waterfall (Studi Kasus: Kantin Universitas Muhammadiyah Papua) - Lintang Harya Tirta Sugara; Heru Sutejo; Edwin; Alfred Tarquo (Tamilis Synex: Multidimensional Collaboration, 2026)
The process of providing menu information, product prices, availability, and ordering services at the Muhammadiyah University of Papua Canteen is still carried out manually, causing difficulties for customers in obtaining information and placing orders efficiently. This study aims to design a web-based online ordering system that provides menu information, prices, and product availability. The research employed the Research and Development (R&D) method with the SDLC Waterfall model, limited to the system design stage. Data were collected through observation, interviews, and documentation. The design process included requirements analysis, UML modeling, database design, and user interface mockups. The results of this study are a system design that enables customers to access product information and place orders online, while administrators can manage products, stock, and orders through an integrated platform. The proposed design is expected to support more effective and efficient canteen services at Muhammadiyah University of Papua.